When MNEs bribe more? The role of managerial discretion - Teng, Da (2024)
Purpose This paper builds upon managerial discretion literature to study the relationship between foreign ownership and bribery intensity. Design/methodology/approach Building on World Bank’s data of 9,386 firms from 125 countries over the period 2006–2018, this paper uses Tobit regression, ordered probit and logit models to empirically test the hypotheses. Findings This paper finds that firms have higher bribery intensity when executives have a higher level of managerial discretion. Smaller firms with slack financial resources tend to bribe more when they face more government intervention, munificent and uncertain industrial environment. Originality/value Extant corruption literature has addressed the effects of external institutional settings and internal corporate governance on bribery offering among multinational enterprises (MNEs). How much, and under what condition do top executives matter in bribery activities are yet to be answered. This paper integrates the concept of managerial discretion with corruption and bribery literature and offers a potential answer to the above question. In addition, prior corruption and bribery literature have primarily studied bribery through either micro- or macro-level analysis. This paper adopts multiple-level of analyses and elucidates the foreign ownership and bribery relationship from the organizational and industrial levels.